Copper-resistant bacteria from industrial effluents and their role in remediation of heavy metals in wastewater - Shakoori, A R; Muneer, B (Folia microbiologica, 2002)
Six copper-resistant bacterial strains were isolated from wastewater of tanneries of Kasur and Rohi Nala. Two strains tolerated copper at 380 mg/L, four up to 400 mg/L. Three strains were identified as members of the genus Salmonella; one strain was identified as Streptococcus pyrogenes, one as Vagococcus fluvialis and the last was identified as Escherichia coli. The pH and temperature optimum for two of them were 7.0 and 30 degrees C, respectively; four strains had corresponding optima at 7.5 and 37 degrees C, respectively. All bacterial isola-tes showed resistance against Ag+ (280-350 mg/L), Co2+ (200-420), CrVI (280-400), Cd2+ (250-350), Hg2+ (110-200), Mn2+ (300-380), Pb2+ (300-400), Sn2+ (480-520) and Zn2+ (300-450). Large-sized plasmids (> 20 kb), were detected in all of the strains. After the isolates were cured of plasmids with ethidium bromide, the efficiency of curing was estimated in the range of 60-90%. Reference strain of E. coli was transformed with the plasmids of the bacterial isolates which grew in Luria-Bertani medium containing 100 mg/L Cu2+. The capability to adsorb and afterwards accumulate Cu2+ inside their cells was assayed by atomic absorption spectrophotometer; all bacterial cells had the ability to adsorb 50-80% of the Cu2+ and accumulate 30-45% Cu2+ inside them after 1 d of incubation.
Keywords: Microbial Sensitivity Tests; Metals, Heavy; biodegradace; Copper; mikrobiální testy citlivosti; antibakteriální látky; Biodegradation, Environmental; Waste Disposal, Fluid; měď; Water Pollution, Chemical; průmyslový odpad; Adsorption; těžké kovy; Anti-Bacterial Agents; Drug Resistance, Bacterial; Industrial Waste; odpad tekutý - odstraňování; bakteriální léková rezistence; Bacteria; adsorpce; chemické znečištění vody